Say No to DMSO: Dimethylsulfoxide Inactivates Cisplatin, Carboplatin and Other Platinum Complexes - Hall, Matthew D. (2014)
The platinum drugs cisplatin, carboplatin and oxaliplatin are highly utilized in the clinic and as a consequence are extensively studied in the laboratory setting. In this study, we examined the literature and found a significant number of studies (11 - 34%) in prominent cancer journals utilizing cisplatin dissolved in dimethylsulfoxide (DMSO). However, dissolving cisplatin in DMSO for laboratory-based studies results in ligand displacement and changes the structure of the complex. We examined the effect of DMSO on platinum complexes, including cisplatin, carboplatin and oxaliplatin, finding that DMSO reacted with the complexes, inhibited their cytotoxicity and their ability to initiate cell death. These results render a substantial portion of the literature on cisplatin uninterpretable. Raising awareness of this significant issue in the cancer biology community is critical, and we make recommendations on appropriate solvation of platinum drugs for research.